Blind lattice‐parameter determination of cubic and tetragonal phases with high accuracy using a single EBSD pattern. Issue 6 (4th October 2018) - Han, Ming; Chen, Chen; Zhao, Guangming; Li, Lili; Nolze, Gert; Yu, Baojun; Huang, Xiaodong; Zhu, Ye
Abstract : A reliable method which can accurately derive the Bravais‐lattice type and lattice parameters of unknown phases from a single EBSD pattern without a priori knowledge is proposed. By solving the geometric relationships in an EBSD pattern based on a huge overdetermined system of equations, error accumulation can be avoided, with the relative errors confined to ∼1% for lattice parameters, <0.4% for axial ratios and ∼0.1° for crystal orientation. Abstract : The Bravais lattices and their lattice parameters are blindly determined using electron backscatter diffraction (EBSD) patterns of materials with cubic or tetragonal crystal structures. Since the geometric relationships in a single EBSD pattern are overdetermined, the relative errors of determining the lattice parameters as well as the axial ratios are confined to about 0.7 ± 0.4% and 0.07 ± 0.03%, respectively, for ideal simulated EBSD patterns. The accuracy of the crystal orientation determination reaches about 0.06 ± 0.03°. With careful manual band detection, the accuracy of determining lattice parameters from experimental patterns can be as good as from simulated patterns, although the results from simulated patterns are often better than expermental patterns, which are lower quality and contain uncertain systematic errors. The reasonably high accuracy is obtained primarily because the detection of the diffracting‐plane traces and zone axes is relatively accurate. The results here demonstrate that the developed procedure based on the EBSD technique presents a reliable tool for crystallographic characterization of the Bravais lattices of unknown phases.